¿What is not talk about when we talk about cryptocurrencies? (Costos y Gestión, 2022)
In a disruptive way, elements that were unthinkable a few years ago appear in the financial markets, which generate significant amounts in transactional markets around the world, without being referred to as legal tender in any country, and high prices are generated with behaviors very volatile.Cryptocurrencies and the network that serves as the basis for this ecosystem to work are born, the DLT (Distributed Registry Technologies), the best known being the Blockchain.In this proposal, the salient aspects will be developed in order to facilitate the understanding of this so-called “crypto ecosystem” and, in particular, the study of the factors that make up the cost matrix of the cryptocurrency validation process.As has already been indicated above, there is a very wide gap in the view of the impact that obtaining some of these cryptocurrencies generates in the environment, due to the indiscriminate use of non-renewable energies, nor what can be the horizon of them in a mutation to renewable energies and if, finally, they will become means of payment or only advance as a reserve of value.
Keywords: cryptocurrencies; blockchain; bitcoin; mining; renewable energies; hashrate; halving